Conventional Dacryocystorhinostomy Versus Pawar’s Implant Dacryocystorhinostomy- A Prospective Study - Chandravanshi, Shivcharan Lal; Shrivastava, Sunil Kumar; Shakya, Devendra Kkumar; Tiwari, Uma Saran (International Journal of Innovative Research in Medical Science, 2019)
Purpose: To compare conventional dacryocystorhinostomy (DCR) with Pawar’s intracystic implant dacryocystorhinostomy in terms of surgical technique, complications and success rate for primary acquired nasolacrimal duct obstruction (NLDO). Materials and Methods: This is a prospective comparative, nonrandomized, clinical study. It is carried out on 50 cases of primary acquired NLDO. The 50 cases were divide into two groups; Group A consisting of 30 cases that underwent Pawar’s intracystic implant DCR whereas Group B consisting of 20 cases those operated by conventional DCR technique. Data regarding demographic profile of patients, mode of presentation, diagnosis, intraoperative variables such as surgical duration, intra- and post-operative complications, hospital stay and causes of failure and final surgical outcome, were analyzed. Clinical success was defined as patent lacrimal system on irrigation (objective) and absence of symptoms (subjective). Results: Out of 50 cases 40 (80%) were female and 10 cases (20%) were males. In this study, 39 (78%) cases had chronic dacryocystitis, followed by pyocele/mucocele 5 (10%), chronic dacryocystitis with lacrimal fistula 3 (6%), and previous failed DCR surgery 3 (6%). Hemorrhage from nasal mucosa was observed in 9 cases (45%) during conventional DCR surgery and one case (3.33%) in implant DCR. Hemorrhage from angular vein occurred in 1 case (5%) during conventional DCR. Nasal mucosa was disrupted/damage in 8 cases (40%) during conventional DCR. The average operating time in convention DCR is 110.50 minutes while for Pwar’s implant DCR is 27.33 minutes. The commonest post-operative complication of Pawar’s intracystic implant DCR was obstruction of passage found in 4 cases (13.33%). Hypertrophic scar was the most common postoperative complication in 8 cases (40%) in conventional DCR. Success rate of implant DCR at 2 months follow up was 83.33% and at the end of 3 months after management of failed cases of implant DCR was 96.66%. Success rate of conventional DCR at 2 months follow up was 80% and at the end of 3 months after management of failed cases of conventional DCR was 85%. Conclusion: The success rate of Pawar’s intracystic implant DCR is comparable with conventional DCR with additional advantages such as easy, quick, minimal intra- and post operative complication and possibility of conventional DCR in future in failed Pawar’s implant DCR.